Roles of Price on Rebates and Implication to Customer Product Choice - Anton Tirta Komara (Jurnal Ekonomi, Bisnis dan Entrepreneurship, 2023)
A comprehensive comprehension of the various factors influencing consumer purchasing decisions is crucial for success in the highly competitive business environment. The findings of this study examine the significant role that price and discounts (rebates) play in consumer decision-making. The study's findings emphasize the considerable influence of price on consumers' decision-making regarding product selection. Consumers tend to seek out more affordable alternative options when there is an increase in the price of a product. Nevertheless, in the event of a compelling discount, consumers tend to transition and opt for the alternative product swiftly.